Uniting hearts and minds: experiences from a pilot festival of youth creative expressions on mental health in India - Shivani Mathur Gaiha; Gulfam Fazlur Rahman; Iram Siddiqui; Vijayluxmi Bose; Sujaya Krishnan (International Journal of Public Health Science (IJPHS), 2023)
Mental-health-related social stigma prevents youth from seeking timely help for mental health problems. The purpose of this study is to assess the feasibility and acceptability of a pilot arts intervention to reduce such stigma among college youth in India. The intervention included three sessions, focused on i) mental health education, ii) developing mental-health-themed art, and iii) a mental-health-themed festival to display art for an invited audience. We assessed feasibility through creation of student-generated art and acceptability in post-intervention surveys and video recordings. The intervention was completed by 371 participants who created 86 works of art (paintings, puppet-shows, drama, dance, and poetry), which was displayed to 434 audience members at uniting hearts and minds: a festival of creative expressions on mental health. Participants self-reported understanding causes and symptoms of mental health problems, interpreting experiences and expressed empathy (n = 194). Our pilot intervention engaged youth, showing potential to reduce mental-health-related stigma and to address feasibility issues related to reaching all colleges uniformly.